2020
DOI: 10.3390/ijerph17165822
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sex Life among People in Taiwan during the COVID-19 Pandemic: The Roles of Risk Perception, General Anxiety, and Demographic Characteristics

Abstract: This study used data collected from an online survey study on coronavirus disease 2019 (COVID-19) in Taiwan to examine changes in sex life during the pandemic and the factors affecting such changes. In total, 1954 respondents were recruited from a Facebook advertisement. The survey inquired changes in sex life during the pandemic, including satisfaction with the individual’s sex life, frequency of sexual activity, frequency of sex-seeking activity, and frequency of using protection for sex. The associations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 53 publications
7
66
0
3
Order By: Relevance
“…Other relevant psychological issues included: increased appetite, reduced libido and higher level of anxiety for health. This corroborates previous evidence [ 16 , 41 43 ]. Among these, health anxiety has been demonstrated to be modulated by psychological flexibility [ 16 ], while eating more seems to be a typical stress related response [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…Other relevant psychological issues included: increased appetite, reduced libido and higher level of anxiety for health. This corroborates previous evidence [ 16 , 41 43 ]. Among these, health anxiety has been demonstrated to be modulated by psychological flexibility [ 16 ], while eating more seems to be a typical stress related response [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, some survey studies investigated sexual function during restrictive social distancing and found how risk perception of COVID-19 was negatively associated with frequencies of sexual activities [38][39][40]. In particular, a higher general anxiety during COVID-19 was showed to have a negative impact on sex life and frequencies of sexual intercourse, decreased satisfaction with sex life and frequencies of sexual activity [41]. These results could explain the use of pornography as an escape from the reality and sexual life crisis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, partnered people who were more knowledgeable about COVID-19 (e.g., knew more about the ways of transmission), and those who engaged in more protective behaviors against infection (e.g., adhered to social distancing), reported a decrease in intercourse and oral sex frequency during the pandemic (Hensel et al, 2020). Moreover, people who perceived more risks related to COVID-19 were more likely to report negative changes in sexual activity during the pandemic (Ko et al, 2020). Following these findings, risk perception and motives for security might be crucial to regulate health in a time when health risks are heightened, determining sexual behavior and predicting sexual risk-taking.…”
Section: Health and Well-being During The Pandemicmentioning
confidence: 99%